2024
DOI: 10.3390/metabo14020117
|View full text |Cite
|
Sign up to set email alerts
|

Anti-Hyperuricemic Effects of Extracts from Chaenomeles speciosa (Sweet) Nakai Fruits on Hyperuricemic Rats

Ruoling Xu,
Peng Deng,
Yiren Ma
et al.

Abstract: Chaenomeles speciosa (Sweet) Nakai (C. speciosa) fruit has medicinal and food applications and exhibits beneficial pharmacological properties. This study aimed to explore the hypouricemic effect of C. speciosa fruit extracts on hyperuricemic rats and uncover potential protective mechanisms. The rats were given hypoxanthine (HX, 100 mg/kg) and potassium oxonate (PO, 300 mg/kg) for 14 days to induce hyperuricemia. Subsequently, the rats were orally administered C. speciosa fruits total extract (CSFTE, 250, 500, … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

0
3
0

Year Published

2024
2024
2024
2024

Publication Types

Select...
4

Relationship

0
4

Authors

Journals

citations
Cited by 4 publications
(3 citation statements)
references
References 42 publications
0
3
0
Order By: Relevance
“…Uric acid levels often rise when renal function declines; therefore, it is considered an important indicator for evaluating kidney function impairment . High-density lipoprotein cholesterol is mainly synthesized by the liver, promoting the reverse transport of cholesterol, carrying excess cholesterol and waste from the blood and tissues to the liver for breakdown and excretion from the body.…”
Section: Resultsmentioning
confidence: 99%
“…Uric acid levels often rise when renal function declines; therefore, it is considered an important indicator for evaluating kidney function impairment . High-density lipoprotein cholesterol is mainly synthesized by the liver, promoting the reverse transport of cholesterol, carrying excess cholesterol and waste from the blood and tissues to the liver for breakdown and excretion from the body.…”
Section: Resultsmentioning
confidence: 99%
“…C. speciosa is a nutritious and beneficial fruit, as well as an important TCM [88]. In recent years, various extraction and purification methods have been used for C. speciosa polysaccharides, and their structures have been characterized by advanced technologies such as NMR, HPLC, and GC-MS. Biologically active substances found in plants may offer health benefits to humans [89].…”
Section: Conclusion and Prospectmentioning
confidence: 99%
“…Recently, a randomized clinical trial demonstrated that quince syrup significantly improved the condition of patients with gastroesophageal reflux disease, whether in children or during pregnancy [ 12 , 13 ]. Several previous preclinical studies have shown that C. sinensis fruits exhibit anti-obesity [ 11 ], anti-inflammatory [ 14 ], antioxidant [ 15 ], anti-ulcerative colitis [ 16 ], anti-osteoarthritis [ 17 ], anti-hyperuricemic [ 18 ], anti-diabetic, including antihyperglycemic and antihyperlipidemic [ 19 ], and anti-aging [ 20 ] activities. These beneficial activities are mainly attributed to polyphenols, including phenolic acids, coumarins, and lignans from C. sinensis fruits [ 21 ].…”
Section: Introductionmentioning
confidence: 99%